Roles of MicroRNAs in Bone Destruction of Rheumatoid Arthritis - Zhao, Hanxiao; Lu, Aiping; He, Xiaojuan (Frontiers in Cell and Developmental Biology, 2020)
As an important pathological result of rheumatoid arthritis (RA), bone destruction will lead to joint injury and dysfunction. The imbalance of bone metabolism caused by increased osteoclast activities and decreased osteoblast activities is the main cause of bone destruction in RA. MicroRNAs (MiRNAs) play an important role in regulating bone metabolic network. Recent studies have shown that miRNAs play indispensable roles in the occurrence and development of bone-related diseases including RA. In this paper, the role of miRNAs in regulating bone destruction of RA in recent years, especially the differentiation and activities of osteoclast and osteoblast, is reviewed. Our results will not only help provide ideas for further studies on miRNAs' roles in regulating bone destruction, but give candidate targets for miRNAs-based drugs research in bone destruction therapy of RA as well.